2022
DOI: 10.1021/acs.joc.2c00903
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Disulfide–Yne and Disulfide–Diazonium Reactions for Potential Direct Modification of Disulfide Bonds in Proteins

Abstract: To find their potential use in protein research, direct addition of a disulfide compound to alkyne (namely disulfide–yne reaction) and S-arylation with arenediazonium salt (namely disulfide–diazonium reaction) were investigated in aqueous or protic solutions. The reaction of dimethyl disulfide with 5-hexynol performed best under 300 nm irradiation in the presence of sodium acetate to afford 5,6-bis­(methylthio)-5-hexenol in 60% yield. Without the prior reduction of a disulfide bond to thiols, the disulfide–yne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…More recently, Fang and coworkers developed a similar HCO 2 Na-promoted strategy for the synthesis of 2-(benzofuran-3-yl)-1,3-dithiepane-5,6-diol 4c starting from 3,4-dihydroxy-1,2dithiane 4a and 2-( propargyloxy)benzenediazonium salt 4b under 450 nm LED irradiation (Scheme 4a). 18 It was confirmed that both sulfur substituents of the product originated from the same disulfide molecule. The protocol was also employed for the modification of trastuzumab antibody through disulfide re-bridging reactions (Scheme 4b).…”
Section: Qiao Sunmentioning
confidence: 87%
“…More recently, Fang and coworkers developed a similar HCO 2 Na-promoted strategy for the synthesis of 2-(benzofuran-3-yl)-1,3-dithiepane-5,6-diol 4c starting from 3,4-dihydroxy-1,2dithiane 4a and 2-( propargyloxy)benzenediazonium salt 4b under 450 nm LED irradiation (Scheme 4a). 18 It was confirmed that both sulfur substituents of the product originated from the same disulfide molecule. The protocol was also employed for the modification of trastuzumab antibody through disulfide re-bridging reactions (Scheme 4b).…”
Section: Qiao Sunmentioning
confidence: 87%
“…Recently, Poulsen et al reported an oxSTEF reagent which generated the bis-thio ketene acetal linked products via double thiol exchange, 19 while Fang et al developed a diazonium salt reagent to generate thioacetal-bridged peptides directly from a disulfide via the photoinduced radical process. 20 All of the above methods were conducted in aqueous buffer systems, which required good water solubility of peptides. Unfortunately, this requirement may not be fulfilled when hydrophobic or aggregation-prone peptides were used as substrates.…”
mentioning
confidence: 99%
“…Unfortunately, this requirement may not be fulfilled when hydrophobic or aggregation-prone peptides were used as substrates . Moreover, the generation of a new chiral center without stereoselectivity at the thioacetal carbon (in Loh’s and Fang’s cases) , or mixture of Z / E isomers (in Poulsen’s case) led to the heterogeneity of the products and may affect the biological evaluation. Developing robust single carbon bis-cysteine rebridging methods without sequence bias and product structural heterogeneity for bioactive peptide cyclization is of great interest.…”
mentioning
confidence: 99%
See 1 more Smart Citation